Dynamic Characteristics and Predictive Capability of Tumor Voxel Dose–Response Assessed Using 18F-FDG PET/CT Imaging Feedback - Chen, Shupeng; Qin, An; Yan, Di (Frontiers in Oncology, 2022)
Purpose: Tumor voxel dose-response matrix (DRM) can be quantified using treatment feedback of serial FDG-PET/CT imaging acquired during radiotherapy. This study investigated the dynamic characteristics and the predictive capability of DRM. Methods: FDG-PET/CT images were acquired before and weekly during standard chemoradiotherapy with the treatment dose 2Gy×35 from 31 head and neck cancer patients. For each patient, deformable image registration was performed between the pretreatment/baseline PET/CT image and each weekly PET/CT image. Tumor voxel DRM was derived using a linear regression on the logarithm of the weekly standard uptake value (SUV) ratios for each tumor voxel, i.e., SUV measured at a dose level that normalized to the baseline SUV0. The dynamic characteristics were evaluated by comparing the DRMi estimated using single feedback image acquired at the i-th treatment week (i = 1, 2, 3, or 4) with the DRM estimated using the last feedback image for each patient. The predictive capability of the DRM estimated using 1 or 2 feedback images was evaluated using Receiver-Operating Characteristic test with respect to the treatment outcome of tumor local-regional control or failure. Results: The mean±SD of tumor voxel SUV measured at pretreatment, 1st, 2nd, 3rd, 4th, and last treatment week was 6.76±3.69, 5.72±3.43, 3.85±2.22, 3.27±2.25, 2.5±1.79 and 2.23±1.27, respectively. The deviations between the DRMs estimated using the single feedback image and the last feedback image were 0.86±4.87, -0.06±0.3, -0.09±0.17, and -0.09±0.12 for DRM1, DRM2, DRM3, and DRM4, respectively. The predictive capability was significant (p<0.027) and increased with the increase of treatment dose level. The DRMs constructed using single feedback image achieved an accuracy of 0.86 ~ 1 quantified using the area under the curve (AUC). The accuracy was slightly improved to 0.94 ~ 1 for the DRMs estimated using 2 feedback images. Conclusion: Tumor voxel metabolic activity measured using FDG-PET/CT fluctuated noticeably during the first 2 treatment weeks and got stabilized reduction rate thereafter. Quantified tumor voxel DRM can be predicted using single FDG-PET/CT feedback image. The predictive capability improved continuously with using one feedback image acquired after the second treatment week (>20Gy) and marginally improved when two feedback images were applied.